Dendritic‐Like Molecules Built on a Pillar[5]arene Core as Hole Transporting Materials for Perovskite Solar Cells. Issue 31 (17th May 2021) - Bettucci, Ottavia; Pascual, Jorge; Turren‐Cruz, Silver‐Hamill; Cabrera‐Espinoza, Andrea; Matsuda, Wakana; Völker, Sebastian F.; Köbler, Hans; Nierengarten, Iwona; Reginato, Gianna; Collavini, Silvia; Seki, Shu; Nierengarten, Jean‐François; et al.
Abstract: Multi‐branched molecules have recently demonstrated interesting behaviour as charge‐transporting materials within the fields of perovskite solar cells (PSCs). For this reason, extended triarylamine dendrons have been grafted onto a pillar[5]arene core to generate dendrimer‐like compounds, which have been used as hole‐transporting materials (HTMs) for PSCs. The performances of the solar cells containing these novel compounds have been extensively investigated. Interestingly, a positive dendritic effect has been evidenced as the hole transporting properties are improved when going from the first to the second‐generation compound. The stability of the devices based on the best performing pillar[5]arene material has been also evaluated in a high‐throughput ageing setup for 500 h at high temperature. When compared to reference devices prepared from spiro‐OMeTAD, the behaviour is similar. An analysis of the economic advantages arising from the use of the pillar[5]arene‐based material revealed however that our pillar[5]arene‐based material is cheaper than the reference. Abstract : Multi‐branched three‐dimensional organic molecules are an appealing class of compounds that can be employed as hole‐transporting materials in high‐performance perovskite solar cells. In this work, two innovative pillar[5]arene‐based HTMs decorated with different triphenylamine fragments are presented. Solar cell performances, stability, and production costs have been deeply investigated with respect to the reference compound spiro‐OMeTAD.